Frictional Properties of Simulated Fault Gouges from the Seismogenic Groningen Gas Field Under In Situ P–T ‐Chemical Conditions. Issue 11 (27th November 2017) - Hunfeld, L. B.; Niemeijer, A. R.; Spiers, C. J.
Abstract: We investigated the frictional properties of simulated fault gouges derived from the main lithologies present in the seismogenic Groningen gas field (NE Netherlands), employing in situ P – T conditions and varying pore fluid salinity. Direct shear experiments were performed on gouges prepared from the Carboniferous shale/siltstone substrate, the Upper Rotliegend Slochteren sandstone reservoir, the overlying Ten Boer claystone, and the Basal Zechstein anhydrite–carbonate caprock, at 100°C, 40 MPa effective normal stress, and sliding velocities of 0.1–10 μm/s. As pore fluids, we used pure water, 0.5–6.2  M NaCl solutions, and a 6.9  M mixed chloride brine mimicking the formation fluid. Our results show a marked mechanical stratigraphy, with a maximum friction coefficient ( μ ) of ~0.66 for the Basal Zechstein, a minimum of ~0.37 for the Ten Boer claystone, ~0.6 for the reservoir sandstone, and ~0.5 for the Carboniferous. Mixed gouges showed intermediate μ values. Pore fluid salinity had no effect on frictional strength. Most gouges showed velocity‐strengthening behavior, with little systematic effect of pore fluid salinity or sliding velocity on ( a–b ). However, Basal Zechstein gouge showed velocity weakening at low salinities and/or sliding velocities, as did 50:50 mixtures with sandstone gouge, tested with the 6.9  M reservoir brine. From a rate and state friction viewpoint, our results imply that faults incorporating Basal Zechstein anhydrite–carbonate material at the top of the reservoir are the most prone to accelerating slip, that is, have the highest seismogenic potential. The results are equally relevant to other Rotliegend fields in the Netherlands and N. Sea region and to similar sequences globally. Key Points: The Groningen field shows a clear mechanical stratigraphy in terms of simulated fault gouge friction coefficient and its rate dependence The slip stability of anhydrite–carbonate‐rich fault rocks is sensitive to pore fluid salinity and sliding velocity The top of the Groningen reservoir is most prone to nucleating seismogenic slip from a rate and state friction point of view